Chemical industry supply chain optimisation using agent-based modelling - Škvor, Jan; Dyntar, Jakub (Univerzita Pardubice, 2013)
In this paper we present an application of Supply Chain Spread Sheet Simulator (SCSS) in a task dealing with chemical industry supply chain redesign and optimisation. SCSS uses principles of Agent-Based Modelling combining 4 types of agents with 3 algorithms to control their behaviour. Location Algorithm is used to place the logistics objects satisfying the demand of customers, Clarke&Wright's Savings Algorithm is applied to plan the routes and Past Stock Movement Simulation is used to control the stock levels. SCSS is developed in MS Excel using programming language Visual Basic for Applications. Its basic functionality is discussed simulating a real task dealing with the redesign of the distribution system for goods coming from chemical industry in the Czech Republic. We test 6 different structures of the distribution system differing in number of located logistics objects ranging from 1 to 6. Based on the outputs of SCSS recalculated to distribution costs we suggest decreasing the number of located warehouses from 6 to 1 estimating almost 33 % distribution costs savings per year.
Keywords: supply chain redesign; agent based modelling; spread sheet simulation; distribution; logistics